2002
DOI: 10.1021/ma020791k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal History and Microdomain Orientation on Deformation and Fracture Properties of Poly(cyclohexylethylene)−Polyethylene Triblock Copolymers Containing Cylindrical PE Domains

Abstract: We investigate the effects of polyethylene cylinder domain orientation and thermal history on the micromechanical deformation and fracture properties of poly(cyclohexylethylene)-poly(ethylene)-poly(cyclohexylethylene) (CEC) triblock copolymer where the poly(cyclohexylethylene) (PCHE) blocks are unentangled. The properties are assessed using a "fragility" test in which copolymer films are strained in tension using a copper grid as a support. Optical microscopy was used to determine the statistics of deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 32 publications
(85 reference statements)
6
72
0
Order By: Relevance
“…360 This was explained by the SCMF theory that for a small difference in the surface energy between two blocks, the entropy penalty associated with the midblock looping in the surface wetting layer for the parallel orientation is larger than the enthalpic penalty arising between two blocks. 361 Once the microdomains are aligned vertically to the substrate, the microdomain size can be easily controlled by either using different molecular weights or adding homopolymers.…”
Section: Block Copolymers In Thin Filmsmentioning
confidence: 99%
“…360 This was explained by the SCMF theory that for a small difference in the surface energy between two blocks, the entropy penalty associated with the midblock looping in the surface wetting layer for the parallel orientation is larger than the enthalpic penalty arising between two blocks. 361 Once the microdomains are aligned vertically to the substrate, the microdomain size can be easily controlled by either using different molecular weights or adding homopolymers.…”
Section: Block Copolymers In Thin Filmsmentioning
confidence: 99%
“…In order to extend the number of varieties of self-assembled nanostructures of BCPs, various approaches have been tried, such as crystallizing semicrystalline BCPs, [35][36][37] selfassembling liquid crystalline BCPs, [38,39] ABC triblock terpolymers [14][15][16] and star copolymers, [40][41][42][43] as well as functionalizing constituent blocks. [44][45][46] Among these, a straightforward way to modify the performance of a BCP is through crystallization of the constituted blocks.…”
Section: Spring-like Behavior Of the Hmentioning
confidence: 99%
“…14 In particular, the mechanical behavior of BCPs with anisotropic ordered structures is further complicated 13,28 because it depends on the extent of long-range ordering and the direction of macroscopic deformation. Because of such morphological complexity, it is difficult to understand the fracture properties of BCPs in terms of their molecular factors.…”
Section: Fracture Studies Of the Ps-b-pmma Bcpsmentioning
confidence: 99%
“…Therefore, the fracture properties of BCPs depend not only on the molecular weight, 9 ordered structure, 10,11 and chain architecture 12 but also on the macroscopic alignment 10,13 and thermal aging. 14 Recent developments in high-performance liquid chromatography (HPLC) for BCPs have enabled the separation of BCPs by chemical composition differences. 15,16 For example, it has been shown that the chemical composition differences of HPLC-fractionated polystyrene-b-polyisoprenes (PS-b-PIs) are as high as 9 wt %.…”
Section: Introductionmentioning
confidence: 99%